THE IMPLEMENTATION OF BALANGAN REGENT REGULATION (PERBUP) NUMBER 91 OF 2021 CONCERNING FREE PUBLIC TRANSPORTATION (A CASE STUDY OF THE SANGGAM TRANSPORTATION SERVICE) - Saidah Hasbiyah; Jumadi Jumadi; Widia Wati (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2025)
In an effort to reduce public dependence on private vehicles and to revitalize the use of public transportation in Balangan Regency, the local government enacted Regent Regulation Number 91 of 2021 concerning Free Public Transportation. While the policy is intended to enhance accessibility, ease congestion, and provide affordable mobility options, its implementation has encountered notable challenges. These include low public engagement, inadequate numbers of operational fleets and supporting infrastructure, and limited inter-agency coordination and public communication. This study applies a descriptive qualitative approach, utilizing interviews, field observations, and document analysis to assess the policy's execution. The results indicate that the implementation has yet to reach its full potential. Several improvements are needed, such as consistent public outreach campaigns, expansion of transportation fleets and facilities, and stronger efforts to raise public awareness regarding the benefits of utilizing free public transit services. Strengthening these aspects could significantly contribute to increased program effectiveness and help foster a shift in community transportation behavior toward more sustainable practices.